(untitled) (Swiss Medical Weekly, 2015)
BACKGROUND: Identification of a Primary Care Physician (PCP) by older patients is considered as essential for the coordination of care, but the extent to which identified PCPs are general practitioners or specialists is unknown. This study described older patients’ experiences with their PCP and tested the hypothesis of differences between patients who identify a specialist as their PCP (SP PCP) and those who turn to a general practitioner (GP PCP). METHODS: In 2012, a cross-sectional postal survey on care was conducted in the 68+ year old population of the canton of Vaud. Data was provided by 2,276 participants in the ongoing Lausanne cohort 65+ (Lc65+), a study of those born between 1934 and 1943, and by 998 persons from an additional sample drawn to include the population outside of Lausanne or born before 1934. RESULTS: Participants expressed favourable perceptions, at rates exceeding 75% for most items. However, only 38% to 51% responded positively for out-of-hours availability, easy access and at home visits, likelihood of prescribing expensive medication if needed, and doctors’ awareness of over-the-counter drugs. 12.0% had an SP PCP, in 95.9% specialised in a discipline implying training in internal medicine. Bivariate and multivariate analyses did not result in significant differences between GP and SP PCPs regarding perceptions of accessibility/availability, doctor-patient relationship, information and continuity of care, prevention, spontaneous use of the emergency department or ambulatory care utilisation. CONCLUSIONS: Experiences of old patients were mostly positive despite some lack in reported hearing, memory testing, and colorectal cancer screening. We found no differences between GP and SP PCP groups.